Hygrothermal Design of Connections in Wall Systems Insulated from the Inside in Historic Building - ORLIK-KOŻDOŃ Bożena (Architecture, Civil Engineering, Environment)
The article presents selected issues related to raising energy standards of historical buildings. Due to their unique character, i.e. historic facades and architectural and decorative elements, the use of typical wall insulation methods, e.g. the ETICS system (External Thermal Insulation Composite Systems), is not possible. One solution is to insulate the external envelopes from the inside. Such an internal application method of insulation in the wall system has a significant impact on the profile of the occurring hygrothermal processes and it can trigger many unfavorable phenomena across the surface of the envelope. The design process and the selection of the type and thickness of insulation are carried out in accordance with commonly used criteria and principles – analogous to those used for newly designed buildings such as meeting minimum thermal insulation defined by the coefficient U and eliminating the risk of surface or interstitial condensation.